IMPLEMENTASI PROGRAM PELAYANAN KESEHATAN GIGI DAN MULUT TERHADAP STATUS KESEHATAN GIGI DI SEKOLAH DASAR 134 / IV KOTA JAMBI - Junaidi Junaidi; Pahrur Razi (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2018)
TITLETHE IMPLEMENTATION OF ORAL AND DENTAL CARE SERVICES PROGRAM TOWARD DENTAL HEALTH STATUS IN ELEMENTARY SCHOOL 134 / IV JAMBI CITYABSTRACTOral and dental care services program is one effort to overcome the problem of oral health. Health Polytechnic Kemenkes Jambi Dental Health Department as an institution of higher education, carrying out the mission of Tridarma Perguruan Tinggi is teaching, research, and dedication to society. As one form of community service that is by implementing an integrated program in the form of dental and oral care programs at elementary school students 134 / IV Jambi City. The purpose of this study was to determine the status of oral and dental health in elementary school students who get and do not get care services of dental and oral care.This research is a quantitative research with cross-sectional study approach, and data collecting from primary data obtained from dental and mouth examination by using a diagnostic set instrument with dental examination format. Samples of research were 30 children of SDN 134 / IV of Jambi who had received dental and oral care services and 30 children of SD 206 / IV of Jambi who was not receiving dental and oral care services with stratified random sampling technique.Results of the average DMF-T SD index that did not get dental care services of teeth is 2. While the average index of DMF-T who get services of nursing care of teeth that is 1. Average OHI-S SD index who do not get service dental nursing care is 1.6. While the average index of OHI-S who get services of nursing care of teeth that is 1.2. The result of a statistical test is the difference of DMF-T and OHI-S index in elementary school students who get with those who do not get dental and mouth nursing care (p 0,05). It is advisable to increase efforts to promote and preventive in primary schools that do not get dental and oral care services. Keywords : Oral and Dental care service